Analisis Pengalaman Pengguna Sistem Informasi ELSIMIL dalam Pendampingan Keluarga Berisiko Stunting di Provinsi Jawa Timur - Fanani, Abdul Fatah; Hariani, Ermatry; Indrihapsari, Hamidah (Journal of Governance Innovation, 2025)
Efforts to accelerate stunting reduction in Indonesia require effective, integrated, and data-driven health information systems. ELSIMIL (Electronic Pre-Marital and Pre-Pregnancy Readiness Application) is an innovation developed by BKKBN to monitor and assist families at risk of stunting (KRS). This study aims to evaluate of ELSIMIL utilization in supporting KRS assistance in East Java Province. A quantitative descriptive research method was applied. Data were collected through an online questionnaire distributed via Google Form to 2,644 respondents consisting of Family Assistance Teams (TPK), as well as sub-district, district/city, and provincial administrators. Descriptive statistical analysis was conducted by referring to six components of the Health Metrics Network (HMN) health information system capacity framework. The findings indicate that ELSIMIL provides significant benefits for KRS monitoring and stunting risk detection, but still faces challenges related to system performance, network accessibility, data security, and interoperability with other health information systems. Strengthening technological infrastructure, enhancing human resource capacity, and implementing cross-sector data integration policies are essential to optimize ELSIMIL’s role as a strategic tool for evidence-based stunting reduction efforts. Keywords: ELSIMIL, health information system, HMN, stunting, health policy